The effect of low-temperature straw-degrading microbes on winter wheat growth and soil improvement under straw return - Huang, Yuanyuan; Yan, Yuanyuan; Ma, Yang; Zhang, Xiang; Zhao, Qian; Men, Mingxin; Huang, Yali; Peng, Zhengping (Frontiers in Microbiology, 2024)
The application of straw-degrading microbes (SDMs) with straw returned to the field is an effective measure to improve soil quality, increase yield, and maintain soil microorganisms. However, the utilization of SDMs in winter in north China is limited by the poor effects at low temperatures. This study investigated the effects of a new compound SDM, including a novel low-temperature fungus Pseudogymnoascus sp. SDF-LT, on winter wheat yield, soil improvement, and soil microbial diversity. A 2-year field experiment was conducted in two different soil textures of wheat–maize rotation fields with full corn straw return and application of SDMs at an amount of 67.5 kg hm−2. After 2 years of continuous application of SDMs, the winter wheat yield increased significantly, reaching 9419.40 kg hm−2 in Ningjin (NJSDM) and 9107.25 kg hm−2 in Mancheng (MCSDM). The soil properties have been significantly improved compared with the single straw return group, especially the sandy loam soil, whose quality is relatively low. The analysis of soil microbial diversity showed that SDMs significantly reduced the Chao1, Shannon, Simpson, and observed species of the sandy loam soil in the MCSDM group. The Simpson and Shannon indexes of fungi diversity in the two experimental sites were significantly increased by SDMs. The negative correlation of fungi increased from 47.1 to 48.85% in the SDM groups. The soil-dominant microbes changed in the SDM groups, in which the interactions between microbes were enhanced. These results suggested that the SDMs changed the the soil microbial community structure and its diversity and complexity, which is beneficial for crop growth. Our study provided sufficient evidence for the utilization of low-temperature SDMs with straw return in cold winter, which plays a role in soil improvement, especially for low-quality soils, to increase crop yield.